-7x-2.8=6x-3.2

Simple and best practice solution for -7x-2.8=6x-3.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-2.8=6x-3.2 equation:


Simplifying
-7x + -2.8 = 6x + -3.2

Reorder the terms:
-2.8 + -7x = 6x + -3.2

Reorder the terms:
-2.8 + -7x = -3.2 + 6x

Solving
-2.8 + -7x = -3.2 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-2.8 + -7x + -6x = -3.2 + 6x + -6x

Combine like terms: -7x + -6x = -13x
-2.8 + -13x = -3.2 + 6x + -6x

Combine like terms: 6x + -6x = 0
-2.8 + -13x = -3.2 + 0
-2.8 + -13x = -3.2

Add '2.8' to each side of the equation.
-2.8 + 2.8 + -13x = -3.2 + 2.8

Combine like terms: -2.8 + 2.8 = 0.0
0.0 + -13x = -3.2 + 2.8
-13x = -3.2 + 2.8

Combine like terms: -3.2 + 2.8 = -0.4
-13x = -0.4

Divide each side by '-13'.
x = 0.03076923077

Simplifying
x = 0.03076923077

See similar equations:

| 8x-2x+x=-5 | | 2x=l-3p | | ×/3-9=1 | | 0.254c-4.331=56.456c | | K+6=J | | x-8.82=3.26 | | -6x-3=x^4+2x^3+2x^2+2x+1 | | 49x^10+x^3-5=0 | | -2(-y+4)+(y-13)= | | 6.1(6.3-3.4h)=4+3(3.9h-1) | | -(1+7m)-6(-7-m)=36 | | 2.3(7.24p-2.7)=5.7-2(p+8.1) | | 6n-18=4(n-3) | | 7(x+7)=0 | | 4.23(m-4.8)=2.56(m+7.91) | | -114+15x=51 | | -2-y+2+y-13= | | 15/3.5=y/9 | | 2tan^2x=3tanx+1 | | (y+3)+3y=3 | | (X-8)+(9x+2)+36=360 | | 2tan(2x)=3tanx+1 | | 4x-10=2x+50 | | 9/8-1/4-2/3 | | 3(2+y)-4=10 | | -5a+6=15 | | (5x+2y)(5x-2y)=25x^2-4y^2 | | (x-8)+(9x-2)+36=360 | | X-23=105 | | 13/15-7/10 | | 3w+7=16 | | -5a+6=12 |

Equations solver categories